Twelve-month prevalence of breastfeeding among infants born in a Baby-Friendly Hospital - Diana Mota-Almeida; Beatriz Costa; Adelaide Taborda (Publicaciones Permanyer, 2023)
Introduction and Objectives: Baby-Friendly Hospitals' initiative upholds practices that promote and protect breastfeeding. Previous studies reveal high breastfeeding rates at discharge from maternity, with a progressive reduction over the first months of life. The objective of this study is to evaluate the epidemiology of breastfeeding during the first year of life and to identify factors that contribute to its maintenance. Methods: An observational, analytical, and cross-sectional study was carried out between February 2020 and March 2021. Data were obtained through a questionnaire carried out during hospitalization after delivery, and periodic telephone contacts during the following months, to assess the maintenance of breastfeeding. Results: This study included 201 mother-child dyads. The prevalence of breastfeeding at discharge was 97.5%; all preterm newborns were breastfed and 83.9% of term newborns were exclusively breastfed. The prevalence of breastfeeding at two, four, six, nine and 12 months was 82.6%, 70.6%, 64.7%, 51.2% and 36.3%, respectively. At six months, breastmilk was the only source of milk in more than 50% of cases, and 19.9% were exclusively breastfed, without complementary feeding. Skinto- skin contact, favorable previous experience and employability were associated with higher breastfeeding rates. Discussion: This study highlights the importance of well-established practices in hospitals, such as skin-to-skin contact, to maintain breastfeeding. It also reveals the need to improve maternity support policies for working women. Reducing breastfeeding rates are responsible for adverse health effects, being its promotion a public health priority.